Computational Fluid Dynamics Simulation Of T-Pipe Scaling Up With Heavy Oil-Water Core-Annular Flow - Muhammad Erzaditya Zhafran; dianita, cindy (Science & Technology Asia, 2025)
Core annular flow (CAF) offers significant energy savings for transporting heavy oils, but its large-scale application in complex geometries remains poorly understood. This study investigates the scale-up of CAF in a T-shaped pipe (T50-50) with water insertion using computational fluid dynamics (CFD). The objective is to evaluate the effects of Reynolds number (Re), Bingham number (Bi), and Froude number (Fr) on flow stability, fouling, and energy efficiency. Simulations employed the Volume of Fluid (VOF) method with the Carreau model to capture shear-thinning behavior. Pipe dimensions were scaled by factors of 1.5 and 5, and performance was assessed through pressure gradient, oil holdup, and energy savings. Results show that maintaining Fr > 1 is essential for concentric CAF stability and fouling reduction. At 1.5x scale-up, oil holdup errors relative to theory were 0–19%, while pressure gradient errors were 19–52%. At 5, errors increased sharply, particularly under Reynolds scaling (up to 554%). Despite this, CAF consistently reduced pumping energy by more than 80%, reaching 98–100% savings. In conclusion, CAF remains an effective strategy for heavy oil transport, with Fr governing stability and Bi providing the best predictor of energy efficiency.